Characterization of the Tobacco Tax - Dias, P. (2024 19th Iberian Conference on Information Systems and Technologies (CISTI), 2024)
This study aims to characterize research on the special tax on tobacco, resorting to a systematic literature analysis. To this end, the Scopus database was used to find articles with the keywords "tobacco" and "taxation," published between 1943 and 2022, resulting in a total of 61 articles for analysis. After studying the articles found, it was possible to conclude that increasing the tax on tobacco is the most effective measure in reducing smoking. On the other hand, several authors also demonstrate that this measure may have negative consequences in certain countries, considering their structure, such as an increase in illegal trade, negative impact on the tobacco industry, and an increase in social inequalities. It was also found that studies related to this topic have been showing a growing trend, as it is a subject that affects public health and is constantly being updated